Trade Liberalisation, Financial Sector Reforms, and Growth (The Pakistan Development Review, 2006)
The relationship between trade liberalisation, financial reforms and economic growth has been well-documented in the economic literature. A considerable body of literature suggests a strong and positive link between trade liberalisation, financial development and economic growth. It has been argued that trade and financial liberalisation policies reduce the inefficiency in the production process and positively influence economic growth. This argument is strengthened by the fact that countries with more open trade and financial policies may grow faster than those with restricted trade and financial policies. An increasing openness is expected to have positive impacts on economic growth [Jin (2000); Fry (1995, 1997); Darrat (1999); Levine (1997); Mckinnon (1973); Shaw (1973) and World Bank (1989)]. There is growing consensus among the researchers that both liberalisation policies are expected to exert positive impacts on economic growth.